ABC's search for the pied piper of consultants - Sharma, Sunil (Professor of business policy); Addepalli, Srinivasa ([London] : SAGE, 2016)
The case provides a rich description of an actual decision-making situation related to selection of a consulting company. An Indian company that has recently acquired a US-based manufacturer of widgets intends to capture 20% market share in the Indian widget market. When in-house efforts did not yield results, the company decided to explore the option of hiring an external consulting firm to develop a growth strategy. The case provides the perspectives of various stakeholders as they examine the various trade-offs involved in the selection of a strategy consultant.
Originally Published in: Sharma, S., & Addepalli, S. (2014). ABC's Search for The Pied Piper of Consultants. BP0376. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Business consultants -- Case studies